Building New Resources After Fire Disasters: The Experience of Fire Survivors - Papadimitriou, Anna; Eirini, Karakasidou (Advances in Social Sciences Research Journal, 2025)
The current qualitative study aims to explore the experience of individuals who survived wildfires, focusing on the meaning they attributed to the wildfire experience, the psychological impact, coping strategies, and the cultivation of positive aspects arising from the experience. Natural disasters, such as wildfires, floods, and earthquakes, constitute traumatic experiences for individuals, as they cause significant losses, such as the loss of lives, property, and environmental destruction, with profound effects on mental health. Nevertheless, there have been limited reports in the research literature suggesting that traumatic experiences can lead to the development of resources and positive elements. This study seeks to examine the overall experience of wildfires. The research involved 12 participants aged 25 to 55 from various regions of Greece, who had experienced wildfire disasters at least five years ago. Semi-structured interviews were conducted and analyzed using the IPA (Interpretative Phenomenological Analysis) method. The findings reveal a wide range of results regarding the meaning-making of the event, the wildfire experience, the psychological consequences, the strategies adopted, and the resources built. As the study of wildfire experiences remains relatively limited, future research should focus on exploring these experiences and highlighting positive elements emerging from trauma. Additionally, it is crucial for governments to implement measures to safeguard the mental health of individuals who survive natural disasters, as well as their families.​